Stakeholder skepticism and pragmatic approaches for True Price Labeling - Carlsson, Sebastian Malte; Hunter, Erik; Arnesen, Edona; Peschel, Anne Odile; Stein, Lennart; Oebel, Benjamin; Gaugler, Tobias; de Jong, Mark; Thøgersen, John (Frontiers in Sustainable Food Systems, 2025)
The global food system generates considerable negative externalities like greenhouse gas emissions, soil degradation, biodiversity loss, and labor inequities. Scholars advocate for internalizing these costs through True Cost Accounting (TCA), which reveals food’s True Price (TP) by reflecting the costs of externalities. Communicating TP to consumers via a True Price Label (TPL) has been proposed, however extant research lacks stakeholders’ insights into TPLs which are necessary for refining TCA methodology. This study explores the attitudes of nine value chain stakeholders across the EU toward supporting, adopting, and (possibly) improving True Price labeling in their organizations. Thematic analysis was used to identify stakeholder skepticism about TP calculations and price impacts as well as pragmatic solutions to mitigate externalities. Overall, the study reveals stakeholder support for TP as a policy instrument, however, more collaboration is needed between researchers and stakeholders when refining TCA methodology and TPL.